RBAU: Noval Redactable Model with Audit Mechanism and Key Update for Alliance Chain - Yineng Chen; Ting Guo; Qingshan Ren; Xiwen Yang; Xiaoxuan Chen; Shukun Liu; Fanzai Zeng (Mathematics)
With the widespread application of alliance chain technology in diverse scenarios, its immutability has gradually revealed certain limitations in practical use. To address this challenge, a redactable alliance chain innovatively introduces functionalities for data modification, deletion, and updating. However, issues related to redaction permissions, auditing, and security hinder its development. To overcome these challenges, the K-medoids clustering algorithm is first employed to select a redaction center and a consensus committee. The redaction center reviews redaction requests, while the consensus committee groups redaction blocks and reaches block consensus. Next, a dual-hash function scheme is proposed, where a subkey-updatable chameleon hash function collaborates with a standard hash function. The system’s master key can revoke a user’s redaction rights by updating their subkey. Based on this framework, a block redaction strategy comprising four phases and nine execution algorithms is introduced, enabling an auditable, accountable, and subkey-updatable RBAU. Security analysis and experimental results demonstrate that the proposed model excels in correctness, resistance to collision of the original key, resistance to collision of the updated key, user subkey updatability, and master key immutability. Additionally, the algorithm’s execution time, transaction execution time, block size, and redaction time are comparable to those of the pre-improvement alliance chain.